Formation of Management-Qualitological Competences Amongspecialists in Education Quality Problem - Кondur Oksana; Ridei, Nataliia; Kuzmenko, Yevhen (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2019)
The article substantiates the existence of a social contract for highly qualified specialists, professionals in quality management in the HEF. On the basis of the introduced definition “model of professional training of future specialists ineducation quality in HEF”, the structural and functional model of the system of professional training of such specialists was developed. The training of quality management professionals is based on the international principles of technical regulation in the fields of education, science and innovation, which determines the application of the ISO standards metric. A two-faceted methodology for organizing the professional training of quality specialists in the HEF is proposed.